ANALYSIS OF THE IMPLEMENTATION OF THE INDEPENDENT CURRICULUM AT VOCATIONAL HIGH SCHOOLS (SMK) CENTERS OF EXCELLENCE - Satriyanto, Kendrat (Journal of Social Research, 2023)
This research aims to analyze the implementation of the Independent Curriculum at the Center of Excellence Vocational High School (SMK). The Merdeka Curriculum is an educational initiative that aims to give schools more freedom in designing curricula that suit students' needs and potential. Center of Excellence Vocational School is a school that focuses on developing excellence in various areas of expertise. The research method used in this study is qualitative descriptive research with a case study approach. Data was collected through interviews with school administrators, teachers, and students of the Center for Excellence Vocational School which has implemented the Merdeka Curriculum. Apart from that, document analysis was also carried out to understand the planning and implementation of the curriculum at the school. The research results show that the implementation of the Merdeka Curriculum at the Center of Excellence Vocational School has provided significant flexibility in designing learning programs that suit student potential. Teachers have a greater role in designing curriculum, identifying student needs, and determining effective teaching methods. Students also benefit from this approach, because they can be more active in choosing subjects that are relevant to their interests and career goals. However, there are several challenges in implementing the Merdeka Curriculum, including the need to ensure that national curriculum standards remain met, develop teacher resources in designing a quality curriculum, and ensure that there is adequate support from schools and the government. This research provides insight into how the Merdeka Curriculum can be successfully implemented at the Center of Excellence Vocational School. These findings can be a reference for other schools that wish to adopt a similar approach to improving the relevance and quality of vocational education.